Manufacture and Initial Characterisation of RAPIDTM Biodynamic Haematogel, an Autologous Platelet and Leukocyte-Rich Plasma Gel for Diabetic Foot Ulcers - Aleksandra Olszewska; Jiajing Duan; Jana Javorovic; K. L. Andrew Chan; James Rickard; Simon Pitchford; Ben Forbes (Gels)
This observational study reports the process for the manufacture of RAPIDTM Biodynamic Haematogel and explores the properties of the platelet and leukocyte-rich plasma gels formed. Gels were manufactured from 60 mL of human blood using the protocol of Biotherapy Services. Platelet and leukocyte content, time-to-gel, gel weight and the temporal profile of liquid exudation from the gels were measured, along with the content of growth factors VEGF and PDGF in the releasate. The effect of the releasate on human keratinocyte (HaCat) cell proliferation was also determined. The platelet and leukocyte concentrations in donor blood were 1.60–8.10 × 108 and 1.00 × 106–2.00 × 107 cells/mL, which were concentrated 2.67- and 1.12-fold, respectively, during processing. Structurally weak gels were formed which exuded a clear liquid releasate (77.4% w/w of gel weight over 60 min) that contained 278 pg/mL VEGF and 1319 pg/mL PDGF. The releasate produced concentration-dependent proliferation of HaCat cells: 5–15% releasate produced a 2.7–8.9-fold increase in growth over 48 h. In conclusion, we have described the point-of-care manufacturing protocol and characterised the gel properties of RAPIDTM Biodynamic Haematogel. This is an essential first step towards identifying, understanding and controlling critical processing parameters that impact on this medicinal product’s quality.